Matija Murko o prvih raziskavah in recepciji indijske mitološke, literarne in jezikovne dediščine pri slovanskih narodih - Petek, Nina (Primerjalna književnost, 2025)
The first part of this paper outlines Matija Murko’s understanding of the importance of ethnography, and the following section focuses in particular on his research into Slovenian folk songs and the foreign motifs present in them, with a special emphasis on the genesis of the Slovenian folk tradition with motifs of India, based on an analysis of the versions of the poem of St. Thomas (Thomas the Apostle) in India, which he presented in his paper “Indija slov-enskih narodnih pesmi” (“The India of Slovenian Folk Songs”). In addition to the Slovenian folk tradition, especially the poetic, and the influence of foreign literatures on Slovenian literature, Murko was also interested in research into the beginnings of the study of Indian culture and Sanskrit in the Slavic area, as he studied comparative grammar of Indo-European languages and Sanskrit in Vienna. Thus, the second part of the paper begins with a brief outline of the reception of Indian cultural and spiritual heritage in nineteenth-century Europe, which also influenced research in the Slavic area. Then, on the basis of Murko’s paper “Prvi uspoređivači sanskrita sa slovenskim jezicima” (“The First Sanskrit Parallels with Slavic Languages”), his findings on Slavic intellectuals who investigated the rich Indian heritage are presented in a concise manner, highlighting the validity and groundbreaking nature of some of the research—despite its “romantic” background, which often led to uncritical and superfi-cial treatments of foreign cultures—both for the beginnings of the formation of Indology as a scientific discipline in the Slavic area and for the investigation of the origins of the Slavs and the strengthening of national consciousness.
Keywords: comparative literature; duhovna dediščina; ethnography; India; Indija; literarna recepcija; literary reception; Murko, Matija; narodopisje; Primerjalna književnost; Slovenian folk songs; Slovenian literary historians; slovenske ljudske pesmi; slovenski literarni zgodovinarji; spiritual heritage; tematologija; thematology